Environmental Issues And Environmental Law Enforcement In Indonesia In The Perspective Of Law Number 32 Of 2009 - Sara, Rineke; Purnama, Bastoni (CV. Publikasi Indonesia, 2024)
The rise of increasingly serious environmental cases, one of which is related to problems in the forestry sector, has prompted the birth of Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH). In this research, the approach used is Juridical-Normative, with a dogmatic type of research, a descriptive research form of legal relations. This research is limited to descriptive-analytical research on criminal policies in environmental law enforcement. The source of all environmental problems is development carried out without paying attention to environmental balance factors which in turn will cause environmental damage and pollution. Legal action taken against perpetrators of environmental pollution and destruction consists of administrative aspects, civil aspects, and criminal aspects. Law enforcement itself needs to be supported by several factors, namely legal means, law enforcement officers, facilities and infrastructure, permits, the Amdal system, and public legal awareness of the environment